2021
DOI: 10.1177/0956797621993108
|View full text |Cite
|
Sign up to set email alerts
|

The Bilingual Advantage in Children’s Executive Functioning Is Not Related to Language Status: A Meta-Analytic Review

Abstract: There is considerable debate about whether bilingual children have an advantage in executive functioning relative to monolingual children. In the current meta-analysis, we addressed this debate by comprehensively reviewing the available evidence. We synthesized data from published studies and unpublished data sets, which equated to 1,194 effect sizes from 10,937 bilingual and 12,477 monolingual participants between the ages of 3 and 17 years. Bilingual language status had a small overall effect on children’s e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 156 publications
6
60
3
Order By: Relevance
“…The main goal of the present study was to determine whether monolingual and bilingual infants differed in their performance on executive functioning skills, that have been reported to be stronger in older bilingual children. Given that a bilingual cognitive advantage has been often reported in young children (but see Lowe et al, 2021), bilinguals were expected to outperform monolinguals on measures of cognitive flexibility (Adesope et al, 2010; Adi-Japha et al, 2010; Bialystok, 2017; Brito et al, 2020; Crivello et al, 2016; Comishen et al, 2019; Poulin-Dubois et al, 2011). More specifically, we hypothesized that bilingual toddlers would outperform monolinguals on tasks involving conflict resolution and shifting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main goal of the present study was to determine whether monolingual and bilingual infants differed in their performance on executive functioning skills, that have been reported to be stronger in older bilingual children. Given that a bilingual cognitive advantage has been often reported in young children (but see Lowe et al, 2021), bilinguals were expected to outperform monolinguals on measures of cognitive flexibility (Adesope et al, 2010; Adi-Japha et al, 2010; Bialystok, 2017; Brito et al, 2020; Crivello et al, 2016; Comishen et al, 2019; Poulin-Dubois et al, 2011). More specifically, we hypothesized that bilingual toddlers would outperform monolinguals on tasks involving conflict resolution and shifting.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, a wide range of tasks measuring executive skills were used (e.g., card sorting, Simon task, Stroop, ANT), and the groups were carefully matched on variables such SES and IQ. A recent meta-analysis conducted on 10,937 bilingual and 12,477 monolingual participants between the ages of 3 and 17 years concluded that the available evidence suggests that the bilingual advantage in children's executive functioning is small, variable, and potentially not attributable to the effect of language status (Lowe, Cho, Goldsmith & Morton, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Gade et al, 2021). This apparent scarcity of metaanalyses in the bilingual language control literature contrasts with the growing number of meta-analyses in other areas of bilingualism research (e.g., the bilingual advantage; Donnelly et al, 2019;Gunnerud et al, 2020;Lehtonen et al, 2018;Lowe et al, 2021;Ware et al, 2020) and also the increase in large-scale studies (e.g., Dick et al, 2019;Nichols et al, 2020). As our systematic review of the four major inhibitory phenomena has shown, however, we lack empirical clarity to some degree in this research area, so that additional meta-analyses and more large-scale studies would be very beneficial for future progress in the field of bilingual language control.…”
Section: Requirements Of a Bilingual Inhibitory Control Markermentioning
confidence: 96%
“…Some studies comparing groups based on these categorical designations have reported that bilinguals performed more accurately or faster than monolinguals on various cognitive tasks and measures, especially those related to executive functioning, whereas other studies found no differences between groups (summary in Antoniou, 2019 ). Both conclusions have been supported by meta-analyses that either confirm the reliability of the group difference (Adesope et al, 2010 ; Grundy and Timmer, 2017 ; van den Noort et al, 2019 ; Grundy, 2020 ; Ware et al, 2020 ; Monnier et al, 2021 ) or fail to reject the null hypothesis (de Bruin et al, 2015 ; Lehtonen et al, 2018 ; Donnelly et al, 2019 ; Lowe et al, 2021 ). One factor contributing to these conflicting results is the definition of “bilingualism” and how participants are assigned to groups in various studies (for discussion see Bak, 2016 ; Bialystok, 2016 ).…”
Section: Introductionmentioning
confidence: 92%